Superstition processes in the province of Cajamarca in the second half of the 18th century - Dammert Bellido, José (1984)
Some time ago I published in the "Allpanchis" magazine, under this heading, three pieces of information about processes for superstitions; Lately I have found a room that starts in the town of Cachén (province of chota).